El cuerpo en la dimensión trágica de la ética psicoanalítica Filosofía y psicoanálisis - Jaramillo Zapata, Jorge Iván (Universidad Católica Luis Amigó, 2022)
The analysis experience starts from the fact that the symptom is presented as something in the body that demands an interpretation. There it is inevitable to lead to a judgment about the most intimate thing that lives in each of us; the unveiling of what consciousness would have preferred to reject. At this point, the body, ethics, and tragedy coincide. It is, then, a journey that starts from the question about the points of encounter and disagreement between philosophy and psychoanalysis concerning ethics, tragedy, and the body as a third party that knots said reflection. The relationship between authors such as Aristotle, Nietzsche, Freud, and Lacan is proposed to reach the specifics of the theoretical elaboration of psychoanalysis, finding there the body as an effect of language and, therefore, with a structure marked by the ineffable that is the cause of the symptom.